en - Indah Pratiwi, Yuli; Asmadiah Lenggana, Fathia; Riani, Hijjah; Irawan Wijaya, Fahri; Dara D, Emeliya Sukma (e-Journal of Linguistics; Vol 17 No 1 (2023): en, 2022)
This study aims to analyze and provide examples of paraphrasing a sentence contained in an article, this article is entitled about the influence of COVID-19 in the world of education and the economy in Indonesia. The article that we take as an example is an article written by our friend. Paraphrases can not only be used in speeches, dialogues, songs of daily life and other literary works, but paraphrases can also be used in a scientific work, for example, in articles, mini-research thesis and others. Therefore, the researcher is very interested in paraphrasing this scientific work, namely the article. This researcher uses a qualitative method, by collecting data, then the researcher paraphrases the sentences that can be paraphrased according to the researcher. then the data is taken and collected, then analyzed with the theory contained in the paraphrase, so it really supports this research. Paraphrasing is the restating of a sentence such that both sentences would generally be recognized as lexically and syntactically different while remaining semantically equal.